Analysis of the Determinants of the Gender Development Index (GDI) in Central Java Province, 2019-2023 - Nabila Athaya Putri; Yuni Prihadi Utomo (Universitas KH. Abdul Chalim Mojokerto, 2026)
The Gender Development Index (GDI) serves as a key indicator to evaluate a country's success in achieving gender equality. This study aims to examine the factors that influence the GDI across Regencies and Cities in Central Java Province during the period 2019 to 2023. The analytical method employed is panel data regression, utilizing data from 35 Regencies/Cities in the province over the specified period. The results indicate that the Fixed Effect Model (FEM) was selected as the best-fitting model, offering high predictive accuracy. Government Expenditure on Health and Education (GSHE), Gross Regional Domestic Product per Capita (GRDP), and the Proportion Men and Women (PW) were found to have a positive on the GDI. Conversely, Women’s Participation in Parliament (WPP), Average Per Capita Education Expenditure (CPEND), Integrated Health Service Posts (POSY), and the Poverty Rate (POVRATE) were not found to have on the GDI. Quality and equitable women's empowerment is key to achieving gender equality. This requires not only adequate funding and quantitative improvements, but also inclusive and gender responsive policymaking.